Activation of a Latent Epitope Causing Differential Binding of Antineutrophil Cytoplasmic Antibodies to Proteinase 3. Issue 5 (7th March 2023) - Casal Moura, Marta; Thompson, Gwen E.; Nelson, Darlene R.; Fussner, Lynn A.; Hummel, Amber M.; Jenne, Dieter E.; Emerling, Daniel; Fervenza, Fernando C.; Kallenberg, Cees G. M.; Langford, Carol A.; McCune, W. Joseph; Merkel, Peter A.; et al.
Abstract : Objective: Proteinase 3 (PR3) is the major antigen for antineutrophil cytoplasmic antibodies (ANCAs) in the systemic autoimmune vasculitis, granulomatosis with polyangiitis (GPA). PR3‐targeting ANCAs (PR3‐ANCAs) recognize different epitopes on PR3. This study was undertaken to study the effect of mutations on PR3 antigenicity. Methods: The recombinant PR3 variants, iPR3 (clinically used to detect PR3‐ANCAs) and iHm5 (containing 3 point mutations in epitopes 1 and 5 generated for epitope mapping studies) immunoassays and serum samples from patients enrolled in ANCA‐associated vasculitis (AAV) trials were used to screen for differential PR3‐ANCA binding. A patient‐derived monoclonal ANCA 518 (moANCA518) that selectively binds to iHm5 within the mutation‐free epitope 3 and is distant from the point mutations of iHm5 was used as a gauge for remote epitope activation. Selective binding was determined using inhibition experiments. Results: Rather than reduced binding of PR3‐ANCAs to iHm5, we found substantially increased binding of the majority of PR3‐ANCAs to iHm5 compared to iPR3. This differential binding of PR3‐ANCA to iHm5 is similar to the selective moANCA518 binding to iHm5. Binding of iPR3 to monoclonal antibody MCPR3‐2 also induced recognition by moANCA518. Conclusion: The preferential binding of PR3‐ANCAs from patients, such as the selective binding of moANCA518 to iHm5, is conferred by increased antigenicity of epitope 3 on iHm5. This can also be induced on iPR3 when captured by monoclonal antibody MCPR2. This previously unrecognized characteristic of PR3‐ANCA interactions with its target antigen has implications for studying antibody‐mediated autoimmune diseases, understanding variable performance characteristics of immunoassays, and design of potential novel treatment approaches. Abstract :